A Study On Various Employee Engagement Programs For Newly Inducted Hoteliers# ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Hotels alone are set to generate 2.3 million jobs both in terms of skilled and non-skilled  manpower. One of the most labour intensive industries in the country where human touch makes a  difference and this crucial factor of human touch cannot be automated. But this human touch comes  with a price which is taking a toll on the employees who work in this stressful industry where service  with a smile defines a brands success in the market. Objective: To explore the various employee  engagement programmes those are being undertaken by hotels to prevent high rate of attrition among  the newly inducted hoteliers. Methodology: Explorative design was followed for the work. Data from  the employees of the hotel industry was collected through questionnaire and telephonic interviews.  Results: The age of the subjects ranged from 21-25 years and was working in the various industries  with the majority (19%) of hoteliers who migrated to Quick Service Restaurants or restaurants,  followed by Information Technology/Information Technology Enabled Services and then followed  by the Retail Industry. Among the other were Banking, Teaching, Reality and Entrepreneurship.  The attrition trends are more alarming because 75% of the people who dropped out of hotels were  recruited as management trainees in various departments. Conclusion: Employee engagement is a  means of improving working lives and organisational performance. Employee engagement is a win win initiative if done properly.
Keywords: Hotels; Employee Engagement; Attrition; Stress; Labour intensive